Modifying maternal sleep position in the third trimester of pregnancy with positional therapy: a randomised pilot trial. Issue 8 (29th August 2018) - Kember, Allan J; Scott, Heather M; O'Brien, Louise M; Borazjani, Ali; Butler, Michael B; Wells, Jesse H; Isaac, Andre; Chu, Kaishin; Coleman, Jerry; Morrison, Debra L
Abstract : Objective: To evaluate whether the percentage of time spent supine during sleep in the third trimester of pregnancy could be reduced using a positional therapy device (PrenaBelt) compared with a sham device. Design: A double-blind, randomised, sham-controlled, cross-over pilot trial. Setting: Conducted between March 2016 and January 2017, at a single, tertiary-level centre in Canada. Participants: 23 participants entered the study. 20 participants completed the study. Participants were low-risk, singleton, third-trimester pregnant women aged 18 years and older with body mass index <35 kg/m 2 at the first antenatal appointment for the index pregnancy and without known fetal abnormalities, pregnancy complications or medical conditions complicating sleep. Interventions: A two-night, polysomnography study in a sleep laboratory. Participants were randomised by computer-generated, one-to-one, simple randomisation to receive either a PrenaBelt or a sham-PrenaBelt on the first night and were crossed over to the alternate device on the second night. Allocation concealment was by unmarked, security-tinted, sealed envelopes. Participants, the recruiter and personnel involved in setting up, conducting, scoring and interpreting the polysomnogram were blinded to allocation. Primary and secondary outcome measures: The primary outcome was the percentage of time spent supine during sleep. Secondary outcomes included maternal sleep architecture, respiration, self-reported sleep position and feedback. Results: The median percentage of sleep time supine was reduced from 16.4% on the sham night to 3.5% on the PrenaBelt night (pseudomedian=5.8, p=0.03). We were unable to demonstrate differences in sleep architecture or respiration. Participants underestimated the time they spent sleeping supine by 7.0%, and six (30%) participants indicated they would make changes to the PrenaBelt. There were no harms in this study. Conclusions: This study demonstrates that the percentage of sleep time supine during late pregnancy can be significantly reduced via positional therapy. Trial registration number: NCT02377817 ; Results.